The Authority of Lampung Provincial Government in Managing Fisheries Resources in Era of Regional Autonomy - Dheni Irawan (Administrative and Environmental Law Review, 2023)
The global COVID-19 outbreak has had a major impact on the marine and fisheries industry in Indonesia. This is also felt by fishermen in Lampung Province with the decline in demand for fishery products in the domestic and international markets in Lampung Province. The overall decline in the fisheries production cycle is influenced by the decline in demand from consumers. The local government has an important role to help restore the condition. The problem in this research is how the authority of the local government of Lampung Province in the management of fisheries resources in the era of regional autonomy and how the efforts of the marine and fisheries office of Lampung Province in an effort to achieve fisheries production in the era of regional autonomy. The research method used is normative research with statute approach. The results of this study are in accordance with the Governor's Regulation on the determination of the main tasks and functions of the Lampung Province Maritime and Fisheries Service as an implementing element of local government in the field of marine and fisheries led by a Head of Service who is responsible to the Governor. he goal is to implement the commitment of the Governor and Deputy Governor elected in 2019-2024 on marine and the Berjaya Fishermen Program to prioritize the welfare of the fishing industry, especially fishermen and their families. The Lampung Provincial Maritime and Fisheries Service provides solutions in the form of feed assistance in collaboration with Lampung University, fish nurseries and distribution in four districts and cities as well as Mobilizing registration and licensing to increase the capacity of fishermen and facilitate licensing and shipping documentation.